Epilepsy Update on Classification, Etiologies, Instrumental Diagnosis and Treatment - Misciagna, Sandro (IntechOpen, 2021)
In the last two decades, there have been enormous advances in understanding epilepsy. Techniques such as electroencephalography, neuroimaging, neurosurgery, and neuropsychology are giving us a better understanding of the pathogenesis of epilepsy. Treatments such as antiepileptic drugs, surgery, and stem cell therapy are improving patient outcomes. This book presents the most current information on the physiopathology, diagnosis, and treatment of epilepsy.